Does the order of presentation of extrinsic and intrinsic quality attributes matter when eliciting willingness to pay? - Garrido, Dolores (2021)
In this study, we estimate consumers' willingness to pay (WTP) for ready meals preserved using microwave assisted pasteurization systems (MAPS)—a novel pasteurization technology, compared to frozen, ready meals. We conducted a laboratory multi-round experimental auction for two samples of ready meal jambalaya in which appearance and sensory evaluation along with extrinsic information was sequentially disclosed to panelists. Our results suggest that when participants tasted the meals and formed an opinion from the meal itself, the liking of appearance and sensory attributes were the most impactful factors for participants' WTP regardless of other available extrinsic (name of the preservation technology and environmental impacts of each technology) attributes. The words “microwave” and “pasteurization” did not negatively impact the WTP. The order in which intrinsic and extrinsic attributes were evaluated and presented did not impact absolute WTP values, but the order did impact the weight of each attribute type on the WTP.